Avaliação da qualidade térmica de praças em Maceió Alagoas : três estudos de caso - Cavalcante, Miquelina Rodrigues Castro (2007)
The aim of this work is to evaluate the thermal quality of urban squares in Maceió city, AL, Brazil, and its relationship with the use of those areas and the thermal sensation of the users. The adopted procedures were the bibliographic review and a field research. In the bibliografic review was set the theoretical reference: the squares´ characteristics, the urban climate and its relationship with human thermal confort. To charachterize those squares it was used the concept of Robba and Macedo´s SQUARE (2002). As a field research after an inventory of the squares in Maceió, AL these squares were chosen and analyzed: Ricardo Lessa´s square, in Tabuleiro dos Martins district; Tenente Madalena´s square, in Cruz das Almas district; and Muniz Falcão´s square, in Ponta Verde´s district. Climate variables were measured and questionnaires were applyed, and behaviour maps were built for January and February, 2006. As thermal confort index it was used the parameters proposed by Fanger (1970). It has been found that thermal quality in square areas is an important factor for their use, specially because they refer to leasure and relaxing areas. This study represents an effort to raise questions and should continue as an investigation object.